Artificial Intelligence-Based Surveillance and Labor Privacy in Indonesia: A Progressive Legal Perspective on Workers’ Rights - Hanifah Ghafila Romadona (Actual Insight, 2025)
The legal issues surrounding labor privacy within Artificial Intelligence (AI)-based surveillance systems have become increasingly urgent in line with the growing use of such technologies to monitor worker productivity. In Indonesia, a significant gap persists between the constitutional guarantee of privacy rights under the 1945 Constitution of the Republic of Indonesia and actual practices in the field, a problem further exacerbated by the absence of specific regulations on AI surveillance. This study employs normative legal research methods with statutory, conceptual, and comparative approaches to examine this gap. The analysis compares Indonesia’s legal framework with Singapore’s Personal Data Protection Act (PDPA) 2012 and Malaysia’s PDPA 2010, using the criteria of transparency, consent, and accountability. Progressive legal theory serves as the analytical foundation, emphasizing the necessity of legal adaptation to safeguard human rights in the digital era. The findings indicate that Singapore and Malaysia provide clearer protections through explicit consent requirements and stringent data governance mechanisms. Accordingly, this study recommends a progressive legal framework based on explicit consent, transparency, and accountability standards to balance business efficiency with workers’ rights.